When we gather = (Ostadahlisiha) : a Cherokee tribal feast - Rogers, Andrea L. (Heartdrum, an imprint of HarperCollins Publishers, 2024)
"One Cherokee child celebrates the family tradition of gathering wild onions for a big community meal, a significant tradition among several southeastern tribes"--